Lack of evidence for methylation of parental and newly synthesized adenovirus type 2 DNA in productive infections. - Wienhues, U (1985)
Methylations of highly specific sites in the promoter and 5' regions of eucaryotic genes have been shown to shut off gene activity and thus play a role in the long-term regulation of gene expression. It was therefore of interest to investigate whether site-specific DNA methylations could also play a role in adenovirus DNA in productive infections. It has been reported earlier that adenovirion DNA is not detectably methylated (U. Günthert, M. Schweiger, M. Stupp, and W. Doerfler, Proc. Natl. Acad. Sci. USA 73:3923-3927, 1976). In the present study, evidence for the methylation of cytidine residues in 5'-CCGG-3' and 5'-GCGC-3' sequences or the methylation of adenine residues in 5'-GATC-3' and 5'-TCGA-3' sequences in intranuclear adenovirus type 2(Ad2) DNA isolated and analyzed early (5 h) or late (24 h) after infection could not be obtained. In Ad2 DNA, 22.5% of all 5'-CG-3' dinucleotides reside in 5'-CCGG-3' and 5'-GCGC-3' sequences. Intranuclear viral DNA was examined by restriction endonuclease cleavage by using HpaII, MspI, HhaI, DpnI, or TaqI and Southern blot hybridizations. The HindIII fragments of Ad2 DNA served as hybridization probes. The data rendered it very unlikely that free intracellular adenovirus DNA in productively infected cells was extensively methylated. Thus, DNA methylation was not a likely element in the regulation of free adenovirus DNA expression in productively infected cells.